Novel treatment strategy for advanced hepatocellular carcinoma: combination of conventional transcatheter arterial chemoembolization and modified method with portal vein occlusion for cases with arterioportal shunt: a preliminary study. (March 2018) - Yasui, Daisuke; Murata, Satoru; Ueda, Tatsuo; Sugihara, Fumie; Onozawa, Shiro; Kawamoto, Chiaki; Kumita, Shinichiro
Background: A novel strategy to combine conventional transcatheter arterial chemoembolization (TACE) and TACE during portal vein occlusion (TACE-PVO) in the presence of high-flow arterioportal shunt (APS) has been developed to treat hepatocellular carcinoma (HCC) with portal invasion. Purpose: To evaluate the efficacy of this strategy. Material and Methods: Twenty-five cases of HCC with portal invasion, treated between April 2006 and December 2015, were evaluated. Balloon occlusion of the portal venous outlet was performed in eight cases of high-flow APS when performing TACE. Conventional TACE was performed in the other 17 cases. The primary endpoint was overall survival. Adverse events and deterioration of liver function were also evaluated. Results: The median survival time (MST) was 12 months. One-, two-, and three-year survival rates were 48.0%, 39.3%, and 26.2%, respectively. Subgroup analysis and multivariate analysis revealed the CLIP score as prognostic factor. MST was 2.5 months in the subgroup with CLIP score ≥4 and 26.0 months in the subgroup with CLIP score ≤3 (hazard ratio = 7.7, 95% confidence interval = 2.3–25.8). Transient elevations of the levels of transaminase and bilirubin were observed; however, deterioration of liver function was infrequent; upgrading of Child-Pugh class in 9.1% of cases. Conclusion: A novel strategy, combining conventional TACE and TACE-PVO, is effective for HCC with portal invasion. The CLIP score may be useful for considering treatment indication.